Deixis in der face-to-face-Interaktion - Stukenbrock, Anja (Linguae & litterae, 2015)
This study develops an empirically founded theory of deixis (words only understandable in context) in the German language. Using a broad base of video documentation from different genres, it investigates the practices of deictic reference as localized, embodied activities in face-to-face interaction. The detailed analyses are systematically referenced to each other and integrated in a comprehensive theoretical framework